Jairus’s Daughter and the Paralytic in Capernaum: Praying for the Dead in Mark and Luke - Löfstedt, Torsten (Svensk teologisk kvartalskrift, 2024)
This paper argues that two passages in Mark and Luke can be used to support intercession for the dead: the raising of Jairus's daughter (Mark 5:21-43; Luke 8:40-56) and the healing of the paralytic in Capernaum (Mark 2:1-12; Luke 5:17-26). In the first account, Jesus encourages Jairus not to give up on his request that Jesus save his daughter even though she has already died. In the second account, the healing of the paralytic, I argue that imagery reminiscent of a funeral is used that encourages the view that Jesus can save a person in response to the faith of those who care for him.